Otomatisasi Kompor Minyak Goreng Bekas Menggunakan Metode VDI.2222 untuk Penguatan Daya Saing UMKM Kuliner - Eko Purwanto Aribowo; Stefanus Hendy Ade Basuki; Benaya Brahmundhito; Valentino Krisnasurya Wicaksana (Badan Riset dan Inovasi Daerah Kota Surakarta, 2025)
The use of subsidized LPG by MSMEs in the culinary sector faces challenges related to availability and price fluctuations. On the other hand, waste cooking oil (used cooking oil) has potential as an alternative fuel source. Unfortunately, existing waste cooking oil stoves still have weaknesses in terms of ignition convenience, time efficiency, and impractical operation. This study aims to design and realize a prototype of an automatic system–based waste cooking oil stove using the VDI 2222 method to make it easier for MSME operators to use. The VDI 2222 methodology was applied in stages, starting from planning, concept development, detailed design, to prototype completion and testing. The design results show that the microcontroller-based automatic system can ignite the stove in an average of 2.6 seconds and extinguish the flame in less than one minute. The fuel pump, igniter, and blower fan circuits are synchronously integrated through a single control button. Performance testing indicates that fuel consumption efficiency increased with an average usage of 0.12 liters of waste cooking oil per hour, equivalent to 30% of conventional LPG energy consumption. This efficiency has the potential to reduce production costs by up to 16%. With a user-centered design approach and automation technology, this prototype offers a viable alternative solution to support energy independence and the sustainable competitiveness of culinary MSMEs.